Visual processing patterns of adults with traumatic brain injury when viewing image-based grids and visual scenes. (3rd July 2019) - Brown, Jessica; Thiessen, Amber; Freeland, Tonya; Brewer, Chung Hwa
Abstract: Many individuals with traumatic brain injury (TBI) rely on augmentative and alternative communication (AAC) supports to meet functional communication needs. The use of images to display message content may be advantageous for this population, given deficits in literacy, visual processing, and cognition. Grid and visual scene displays are two options for presenting images within AAC systems. Eye-tracking technology was utilized to evaluate the visual processing patterns of 13 adults with a history of TBI and 13 adults without TBI when interpreting themes depicted in grid and visual scene displays. Results indicated that differential processing and effort was required when interpreting the two display types. Both groups of participants required significantly more visual fixation time and exhibited patterns consistent with greater cognitive effort when identifying themes depicted in grids compared to visual scenes (i.e., greater numbers of short fixations). The participants with TBI were overall less efficient than those without TBI when identifying themes presented in both AAC display types. These results add to the growing body of evidence indicating that visual scenes may more effectively represent complex concepts than decontextualized, grid-based images for individuals with TBI. Additional clinical implications are discussed.